Adverse commoning: Tracing contested legal geographies of the urban commons. (February 2022) - Noterman, Elsa
Under threat of enclosure in rapidly gentrifying cities, some urban commoners are turning to legal tactics to ward off dispossession. In this article, I explore the contested legal geographies of urban commoning, considering some of the challenges, stakes, and opportunities that emerge in the effort to gain legal recognition. Specifically, I examine the use of the doctrine of adverse possession by Philadelphia gardeners to claim title to the community farm they cultivated as an urban commons for decades. In the context of a neoliberal settler colonial city, I argue that the gardeners' adverse commoning, involving an il/legal counterclaim to property, facilitates consideration of the ways urban commoners are both enrolled in normative property regimes and have the potential to resist these regimes through errant performances of proprietary continuity, exclusivity, notoriety, and hostility.